Morphometric and Meristic Analysis of Rasbora in East Java Province - P Kumaladewi; Mufasirin; Nunuk Dyah Retno Lastuti; Mochammad Amin Alamsjah; Win Darmanto; Sapto Andriyono (Department of Aquaculture, 2022)
Rasbora (Rasbora sp.) is one of the endemic freshwater fish species in East Java, which is currently being threatened due to environmental degradation, human activities and pollution. In East Java, it is known that there are several species of Rasbora (Rasbora sp.). Domestication is one method to preserve Rasbora in East Java, preceded by identifying potential species of Rasbora sp. from the natural catchment. This study aims to determine the diversity of Rasbora sp in East Java. Samples were taken at five different locations, specifically: Nganjuk (Brantas Watersheds), Ngawi (Bengawan Solo Watersheds, Silowo Springs Tuban, Umbulan Springs Pasuruan and the Setail Watersheds Banyuwangi. The main parameters observed were morphology and morphometry. The morphological analysis used identification guidelines, while morphometric data were obtained through 15 parameters measurement then analyzed using one-way Anova test on SPSS 25 software. Based on the morphological and morphometric analysis, it is known that the species of Rasbora in Nganjuk and Ngawi regencies are Rasbora argyrotaenia and the species of Rasbora in Tuban, Pasuruan and Banyuwangi regencies are Rasbora lateristriata. One-way Anova test showed Rasbora from the five locations were significantly different based on the result value of p<0.05.